2014
DOI: 10.4103/0972-124x.131327
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the role of antibiotics in preventing postoperative complication after routine periodontal surgery: A comparative clinical study

Abstract: Background and Objectives:Aim of this randomly controlled clinical study was to evaluate the role of antibiotics to prevent postoperative complications after routine periodontal surgery and also to determine whether their administration improved the surgical outcome.Materials and Methods:Forty-five systemically healthy patients with moderate to severe chronic periodontitis requiring flap surgery were enrolled in the study. They were randomly allocated to Amoxicillin, Doxycycline, and control groups. Surgical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
6
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…In fact, the complications registered were even more frequent in the “antibiotic group” [56, 57, 60–62], in which 25% of the GTR and 17.8% of the EMD group presented membrane exposure/dehiscence and/or swelling. This is coincident with a previous clinical study [82] that evaluated the role of antibiotics in preventing early post-operative complications after periodontal surgical procedures. The evaluation was performed 1, 2, 4, 7 days and 3 months after surgery and 3 groups were evaluated (amoxicillin, doxycycline and no antibiotics).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In fact, the complications registered were even more frequent in the “antibiotic group” [56, 57, 60–62], in which 25% of the GTR and 17.8% of the EMD group presented membrane exposure/dehiscence and/or swelling. This is coincident with a previous clinical study [82] that evaluated the role of antibiotics in preventing early post-operative complications after periodontal surgical procedures. The evaluation was performed 1, 2, 4, 7 days and 3 months after surgery and 3 groups were evaluated (amoxicillin, doxycycline and no antibiotics).…”
Section: Discussionsupporting
confidence: 83%
“…Another important parameter is the administration of systemic medications and especially antibiotics after or during the surgical procedures. While a few studies concluded that better healing and less discomfort is observed when antibiotics were given [77, 78], in many other studies [7982] the use of antibiotics was considered not necessary. Although there is currently no consensus regarding this aspect, this parameter was assessed in the present review (Table 6) in order to avoid a possible bias but, given that in all studies drugs and posology were vastly different, establishing any conclusion from the given data seems inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…Studies conducted by Ng and Bissada[3] and Mohan et al [11] showed similar results with the use of doxycycline.…”
Section: Discussionmentioning
confidence: 57%
“…These results are in accordance with a study done by Mohan et al in 2014 which compared doxycycline over amoxicillin and placebo and found no significant change in PI and GI between the three groups post surgery. [11]…”
Section: Discussionmentioning
confidence: 99%
“…I read with interest article entitled “evaluation of the role of antibiotics in preventing postoperative complications after routine periodontal surgery: A comparative clinical study” authored by Dr. Mohan et al . [ 1 ] in the March-April 2014 issue of Journal of Indian Society of Periodontology.…”
mentioning
confidence: 99%